RESOLUSI KONFLIK PEDAGANG KAKI LIMA DI KAWASAN UNIVERSITAS TELKOM DENGAN PENDEKATAN GRAPHIC MODEL WITH MULTI-ATTRIBUTE RATING DAN TEORI DRAMA - Dina Yosiana; Abdullah Abdullah (Lembaga Penelitian Universitas Langlangbuana, 2020)
This research aims to give recommendation to Telkom University in order to solve conflict about street vendor (PKL), which sells in Telkom University area. In this research combined Graph Model for Conflict Resolution (GMCR) and Simple Multi Attribute Rating Technique (SMART) approach. The combination GMCR and SMART are referred as Graphic Model with Multi-attribute Rating (GMMR). GMMR can quantitatively measure the increase profit by a player when he choose a certain resolution scenario. This research use qualitative method, with data collection method is indepth interview from the interviewees. In this research, they are 4 players, government, street vendors (PKL), LSM GMBI, and YPT. Base on the analysist that has been done, with using GMMR method, we can get the best scenario, scenario 1 which profitable to all the players. And the result form drama theory is 16 dilemmas in existing condition, but the condition can be done with the scenario from GMMR method. The conclusion from this research is the resolution conflict with win-win solution which result happy ending for all players with equilibrium scenario, Yayasan Pendidikan Telkom will provide the place for relocation and not to close the public road, government must be limit the amount of street vendors, LSM GMBI must not demo, and the street vendors must move to the relocation